Pemeriksaan Kadar Glukosa Darah Sewaktu, Kadar Asam Urat dan Kadar Cholesterol pada Masyarakat di Desa Eretan Wetan Kabupaten Indramayu Periode Februari 2020 - Adolfina R. Amahorseja; Ance Adriani; Jumaini Andriana; Rospita Adelina Siregar (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2020)
The implementation of PkM FKUKI Jakarta is located in the village office of Eretan Kulon Village, on Saturday, February 22, 2020, beginning with "Counseling Health Services and Legal Protection for Women's Reproductive Health" delivered by dr. Rospita Adelina Siregar, MH.Kes. with an audience of mothers / women numbering 150 people, the feedback obtained included that the community did not understand their reproductive rights, the community did not understand the application of their reproductive rights, in determining the method of family planning, determining the number of children, the probable cause of low education, most did not graduated elementary school. The activity was continued with free treatment for 938 people, consisting of adult and child age groups, this activity was served by a health team from FKUKI, namely: Dr. Adolfina R. Afhorseja, MS: Dr.Ance Adriani, MS.Sp.OK., Sp. GK and Dr. Jumaini Andriana, MPd. Ked. also blood tests for 492 patients on the indication served by the GKJ health team (PIC.drg. Sri Rahayu and Dr. Sri Udaneni), with details: the number of patients undergoing Blood Sugar examination as many as 207 people, Uric Acid 159 people, and examination of levels Cholesterol 105 people, Conclusion: When Glucose Levels <145 mg / dl are 127 people (61.4%), Uric Acid Levels (5-7 mg / dl) = Normal, 116 people (73%), and Cholesterol Levels ( <200 mg / dl) = Normal, as many as 60 people (57.1%). Keywords: counseling, treatment, reproductive rights, women